Analisi Perubahan Sikap Turki Terhadap Aksesi Swedia Bergabung dengan NATO - Muhdiyaningsih, Ayu Fatimah; Retnowatik, Frentika Wahyu (Jurnal Ilmiah Widya Sosiopolitika, 2025)
This research explains Turkey’s change in attitude towards Sweden’s accession to NATO. This research aims to provide an understanding of the reasons underlying the changing Turkey Attitude, which initially rejected and then accepted Sweden’s accession. This type of research uses explanatory with primary and secondary data sources. The data analysis technique used is qualitative, and the theory used by the author is the theory of Decision Making by Hans J. Morgenthau and Institutional Bargaining by Robert Dahl. The results of this study explains that from a Decision Making perspective there are 2 (two) reasons for Turkey’s rejection of Sweden’s accession, namely the first that Turkey wants to secure a counter-terorism agreement with Sweden, especially related to terrorist activities carried out by the PKK group, this’s done as a step to combat the threat of regional terrorism. Then the second reason is Turkey’s desire to regain access to military technology and equipment, especially the F-16 fighter aircraft owned by the United States which had stopped. In additional, the research results from the Institutional Bargaining perspective, namely, Turkey want it’s accession to European Union to be launched. As it’s known that Turkey has long wanted membership in the EU, but this has been an obstacle, so with the denial of accession to Sweden, which is also a member of the EU, this moment is used by Turkey as a bargaining tool for its membership.